Alteration of gut microbial composition associated with the therapeutic efficacy of fecal microbiota transplantation in Clostridium difficile infection - Pei-Chang Lee; Tien-En Chang; Yen-Po Wang; Kuei-Chuan Lee; Yi-Tsung Lin; Jen-Jie Chiou; Chi-Wei Huang; Ueng-Cheng Yang; Fen-Yau Li; Hui-Chun Huang; Chun-Ying Wu; Yi-Hsiang Huang; et al. (Journal of the Formosan Medical Association, 2022)
Background/purpose: Clostridium difficile infection (CDI) leads to a significant cause of hospital-acquired morbidity and mortality. Fecal microbiota transplantation (FMT) is effective to treat recurrent or refractory CDI (rCDI). However, the change of microbial composition contributed by FMT and its association with treatment outcomes is not well determined in Taiwan. We aimed to investigate the efficacy of FMT and the association with microbial alteration endemically. Methods: Twelve patients who received FMT for rCDI in Taipei Veterans General Hospital were prospectively enrolled from April 2019 to July 2020. The clinical assessments and fecal microbial analyses in comparison with fecal materials of unrelated donors were conducted before and after FMT. Results: The overall success rate of FMT for rCDI was 91.7%. A prominence of Proteobacteria, Gammaproteobacteria and Enterobacteriales were observed in the feces of patients with rCDI. Increased fecal phylogenetic diversities and a significant microbial dissimilarity were provided by successful FMT compared to patients before treatment. However, the distinctness was not obvious between patients’ feces at baseline and after unsuccessful FMT. Moreover, dynamic change of fecal microbial composition after FMT was observed during follow-up but did not interrupt the treatment effects of FMT. Conclusion: Gut dysbiosis commonly co-exists in patients with rCDI. Restoration of gut microbial communities by FMT provides a promising strategy to treat antibiotic-failed CDI, and the extent of microbial change would be related to the treatment outcomes of FMT. Besides, the effectiveness of FMT for CDI could be maintained even the gut microbiota has diverged over time.